Of Roses and Jasmine – Auto-ethnographic reflections on my early bilingual life through China's Open-Door Policy. Issue 5 (3rd September 2018) - Lu, Jinjin
ABSTRACT: China's Open-Door Policy has brought significant changes in terms of economic, education and cultural development both inside and outside China, creating valuable opportunities for understanding the cultural stereotypes Asians and Westerners have about each other. In this paper, I interrogate my experiences as an English as a foreign language (EFL) learner and then as a lecturer in multilingual and multicultural environments from the early 1990s until a lecturer in a Chinese university in the twenty-first century. My series of auto-ethnographic dialogues between a cast of characters, recalling experiences, perceptions and emotions provides readers with opportunities to actively respond to the text. Through this auto-ethnographic memoir and performance, I hope to contribute to new directions for narrative research in intercultural contexts.